DT, BIM, and IoTs Contributions and Barriers in Construction PM: A PRISMA - Abdulqader, Marwan; Bin Alias, Aidi Hizami; Haron, Nuzul Azam; Zuhri, M. Y.M. (Sciendo, 2026)
Developed nations noticed pivotal relevance of Construction 5.0 through various cutting-edge digital solutions, contributing to promoted progress control and various alleviated risks. This offered a road map for developing countries to implement such strategies for amended construction project management (PM). Out of all these breakthroughs, digital twin (DT), building information modeling (BIM), and the Internet of Things (IoTs) have been extensively introduced lately. Construction PM aims to organize complex enterprise tasks, alleviate delays and cost overruns, and reduce controversies that could cause court claims and lengthy disputes. This paper utilizes PRISMA to highlight diverse DT, BIM, and IoT implementation impediments in developing lands, providing key statistics, influential insights, and possible plans of action to adopt DT, BIM, and IoTs flexibly in construction. The PRISMA results revealed that DT supplies project managers with a clear image concerning potential opportunities and risks of construction projects before being executed. BIM enables full visualization of the project. It fosters influential collaboration and understanding among parties. It raises productivity. Cheap IoTs sensors can be installed at critical project locations to record real-time data and track the progress. Simulations can predict future progress scenarios from these data. Since construction has the low pace of digitalization globally, evidence-based practices are still needed. Thus, consultants, contractors, and project managers can adopt these dynamic Construction 5.0 tools.